Looking Forward in Candidate Gene Research: Concerns and Suggestions. Issue 2 (April 2015) - Schlomer, Gabriel L.; Cleveland, H. H.; Vandenbergh, David J.; Fosco, Gregory M.; Feinberg, Mark E.
<x xml:space="preserve">Abstract</x> Candidate Gene × Environment (cGxE) interaction research holds promise for helping us understand for whom and why environments matter for families and development. In their commentary on our target article (G. L. Schlomer, G. M. Fosco, H. H. Cleveland, D. J. Vandenbergh, & M. E. Feinberg, 2015), J. E. Salvatore and D. M. Dick (2015) present their view of the current state and future of cGxE research and frame the debate regarding its merits for advancing knowledge of gene–environment interplay. In this reply, we discuss points of agreement and departure and provide a list of 5 domains by which the quality of cGxE research should be evaluated. Our hope is that researchers will use this list as a guide for their own work.